Lasmiditan for single migraine attack in Japanese patients with cardiovascular risk factors: subgroup analysis of a phase 2 randomized placebo-controlled trial. Issue 12 (2nd December 2022) - Hashimoto, Yoichiro; Komori, Mika; Tanji, Yuka; Ozeki, Akichika; Hirata, Koichi
ABSTRACT: Background: Some migraine treatments are contraindicated for patients with cardiovascular disease (CVD) or risk factors (CVRFs). We report safety and efficacy of lasmiditan, a new oral acute migraine treatment with no cardiovascular contraindication, in Japanese patients with CVRFs. Research design and methods: MONONOFU was a multicenter, randomized, double-blind, placebo-controlled, phase 2 study of Japanese patients with migraine (met International Headache Society criteria, Migraine Disability Assessment score ≥11, disabling migraine for ≥1 year). Eligible patients were randomized (7:3:7:6) to placebo or lasmiditan 50, 100, 200 mg. This prespecified analysis described CVDs, CVRFs, and cardiovascular treatment-emergent adverse events (TEAEs). Efficacy (proportion pain-free, experienced pain relief, most bothersome symptom-free, or disability-free 2 hours post-dose) was evaluated within CVRF subgroups (≤1, ≥2). Results: Of 846 randomized patients, 691 were analyzed (CVRF≤1: 375; CVRF≥2: 316). The proportion of lasmiditan-treated patients with ≥1 TEAE was not related to CVRF numbers. Eighteen (3.8%) lasmiditan-treated and three (1.4%) placebo-treated patients reported likely cardiovascular TEAEs. Lasmiditan was more effective than placebo at relieving pain, symptoms, and disability in both CVRF subgroups. There was no consistent relationship between CVRF subgroups and efficacy. Conclusions: Lasmiditan was well tolerated and effective in Japanese patients with migraine and CVRFs. Trial registration: ClinicalTrials.gov: NCT03962738.